Combination of Phycocyanin, Zinc, and Selenium Improves Survival Rate and Inflammation in the Lipopolysaccharide-Galactosamine Mouse Model - Oner, Pinar; Er, Besir; Orhan, Cemal; Şahin, Kazım (Springernature, 2023)
Sepsis is related to systemic inflammation and oxidative stress, the primary causes of death in intensive care units. Severe functional abnormalities in numerous organs can arise due to sepsis, with acute lung damage being the most common and significant morbidity. Spirulina, blue-green algae with high protein, vitamins, phycocyanin, and antioxidant content, shows anti-inflammatory properties by decreasing the release of cytokines. In addition, zinc (Zn) and selenium (Se) act as an antioxidant by inhibiting the oxidation of macromolecules, as well as the inhibition of the inflammatory response. The current study aimed to examine the combined properties of Zn, Se, and phycocyanin oligopeptides (ZnSePO) against lipopolysaccharide-D-galactosamine (LPS-GalN)-induced septic lung injury through survival rate, inflammatory, and histopathological changes in Balb/c mice. A total of 30 mice were allocated into three groups: normal control, LPS-GalN (100 ng of LPS plus 8 mg of D-galactosamine), LPS-GalN + ZnSePO (ZnPic, 52.5 mu g/mL; SeMet, 0.02 mu g/mL; and phycocyanin oligopeptide (PO), 2.00 mg/mL; at 1 h before the injection of LPS-GalN). Lung tissue from mice revealed noticeable inflammatory reactions and typical interstitial fibrosis after the LPS-GalN challenge. LPS-GalN-induced increased mortality rate and levels of IL-1, IL-6, IL-10, TGF-beta, TNF-alpha, and NF-kappa B in lung tissue. Moreover, treatment of septic mice LPS-GalN + ZnSePO reduced mortality rates and inflammatory responses. ZnSePO considerably influenced tissue cytokine levels, contributing to its capacity to minimize acute lung injury (ALI) and pulmonary inflammation and prevent pulmonary edema formation in LPS-GalN-injected mice. In conclusion, ZnSePO treatment enhanced the survival rate of endotoxemia mice via improving inflammation and oxidative stress, indicating a possible therapeutic effect for patients with septic infections.
Keywords: Zinc; Selenium; Spirulina; Inflammation; LPS